TRANSFORMASI PENDIDIKAN DAN EKONOMI DI YAYASAN AL-JADID KELURAHAN BARU MELALUI KOLABORASI AKSI SOSIAL DAN PENGETAHUAN INOVATIF - Jannah, Eneng Raudatul; Qawly, Hafiz Iftitah; Robbani, Hamdan Thufail; Burhanurobbi, Irsyad; Fauziah, Tiara Dilla; Nisa, Nachdiatun; Rahmadita, Nurmalia; Barkah, Lia; Nurwandi, Rhefky Al Jihad; Fajar, Muhammad; Shofariyani, Shobah (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Education is very important for human development completely to educate and improve the life of the nation. Social Work Lectures (KKS) are a concrete manifestation of the duties of lecturers and students in implementing the Tri Dharma of Higher Education, namely the service aspect. Through community service activities in Baru Village, one of which is the Al- Jadid Foundation, there is synergy between universities and the community as a form of democratic knowledge. The aim of this KKS activity is to move away from the traditional education model which is one size fits all and focuses on providing personalized learning paths for students so as to optimize educational and economic values ​​in empowering society. KKS is carried out through activities: hydroponic empowerment, KKS teaching RA and TPQ, socialization of student savings, Ar Riyadh Lil Sihhah (gymnastics), making wall panels, Arabic language socialization, sharia banking seminars, cleaning mosques, and Islamic arts performances. The results of the service provide an illustration of the increasing enthusiasm of children, teachers, the community and Foundation officials in socializing and implementing Islamic-based education.